Memoirs / Clara Malraux. - d (London : Bodley, 1966)
Part of a typescript draft of the autobiography of Andre Malraux, published in 1967 as "Antimemoires". The pages relate to three separate sections of the book namely "Les Noyers de l'Altenbourg," "La Tentation de l'Occident" and "La Condition humaine".
Manuscript reference no. : NLA MS 2232.
In French.
French writer, government official, archaeologist, hero of antifascist resistence in Spanish Civil War and World War II. Writer of fictional and non-fictional works including "Condition humaine", "Tentation de l'Occident" and "Noyers de l'Altenbourg". Minister of Information, 1945-1946, Minister of State responsible for culture, 1959-1969.
Keywords: d; Novelists, French -- 20th century -- Biography; Statesmen -- France -- Biography; Civilization, Modern -- 20th century